Sorafenib is an antagonist of the aryl hydrocarbon receptor. (30th March 2022) - Wei, Kuo-Liang; Gao, Guan-Lun; Chou, Yu-Ting; Lin, Chih-Yi; Chen, Shan-Chun; Chen, Yi-Ling; Choi, Hui Qin; Cheng, Chi-Chia; Su, Jyan-Gwo Joseph
Abstract: Sorafenib is an orally administered inhibitor of several tyrosine protein kinases. Treatment with sorafenib induces autophagy, which may suppress the growth of hepatocellular carcinoma (HCC) and other cancers. Aryl hydrocarbon receptor (AhR) is activated by xenbiotics and is involved in detoxification, but also plays other physiological roles. The following results were obtained. ITE and β-NF are endogenous and synthetic AhR ligands, respectively. One μM sorafenib can strongly suppress baseline as well as 0.5 μM ITE- and 1 μM β-NF-induced transcriptional activity of the aryl hydrocarbon response element (AHRE) in both human and mouse cells. Cytochrome p450 (CYP) 1A1 is mainly transcribed by activated AhR. Sorafenib (2−15 μM) strongly and dose-dependently suppressed baseline as well as 2 μM ITE- and 10 μM β-NF-induced CYP1A1 mRNA and protein expression. Ligand-activated AhR translocates from the cytoplasm to the nucleus. While sorafenib was found to suppress AhR activity, the drug alone was able to induce AhR translocation into the nucleus. Sorafenib's antagonistic action on AhR was comparable to that of the known AhR antagonist CH-223191 in human liver and ovarian cell lines. In summary, we demonstrate that sorafenib is a potent AhR antagonist and likely endocrine disruptor of the AhR. Moreover, sorafenib offers potential benefit for diseases treatable through AhR suppression strategies. Further investigation is warranted into sorafenib's AhR antagonistic behavior.